Coalition Formation in Games without Synergies - Marco Marini; Sergio Currarini (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper establishes sufficient conditions for the existence of a stable coalition structure in the coalition unanimity game of coalition formation, first defined by Hart and Kurz (1983) and more recently studied by Yi (1997, 2000). Our conditions are defined on the strategic form game used to derive the payoffs the game of coalition formation. We show that if no synergies are generated by the formation of coalitions, a stable coalition structure always exists provided that players are symmetric and either the game exhibits strategic complementarity or, if strategies are substitutes, the best reply functions are contractions. We illustrate the role of synergies in a Cournot oligopoly example with cost reducing R&D.
Keywords: C7; 330; Coalition formation; Synergies; Strong Nash equilibrium; Koalition; Spieltheorie; Nash-Gleichgewicht; Oligopol; Synergie